Material Flow Management Improving Cost Efficiency and Environmental Performance - Hinz, Kristin; Wagner, Bernd; Enzler, Stefan; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD, 2006)
The implementation of material flow management offers enterprises a high potential for realizing new economic competitive advantages. The eco-efficient optimization of material flows aims at reducing costs while simultaneously achieving long-term sustainability with regard to ecological and societal aspects. Knowledge of existing methods and the latest trends is a key prerequisite for successfully implementing, refining and disseminating material flow management approaches. This book summarises the fundamental concepts and tools of material flow management and presents the newest methods and findings. Case studies illustrate the results from recent research projects conducted in cooperation with industrial companies. The book thereby provides an up-to-date overview of the subject of material flow management for science and practice.
Aspects of Material Flow Management -- Computer Aided Resource Efficiency Accounting -- Measuring Environmental Performance with EPM-KOMPAS Software Tool $1 (BMaterial Flow Analyses, Environmental Assessment and Success Control -- Integrated Controlling Based on Material and Energy Flow Analysis $1 (BA Case Study in Foundry Industries -- Environmental Accounting Instruments: Implementation & Continuous Use $1 (BConcepts for the Application of Input-Output Balance, Environmental Performance Indicators and Flow Cost Accounting -- Efficient Closure of Material and Component Loops $1 (BSubstance Flow Oriented Supply Chain Management -- Developments in Material Flow Management: Outlook and Perspectives.s
Keywords: Business; Accounting; Bookkeeping; Production management; Environmental economics; Business and Management; Operations Management; Environmental Economics; Accounting/Auditing.; Electronic books